Proceso de terapia existencial de artes expresivas - Mayorga González, José Miguel (2020)
The following article focuses on understanding the process of Existential Therapy of Expressive Arts, exploring from a documentary analysis topics such as imagination, experience, modes of expression, poor experimentation, all of the above, from a phenomenological perspective- existential, focused on helping the client to explore and understand existence as a continuous and complex relational mystery, which requires constant reflection, to assume life with ownership and responsibility.